2014
DOI: 10.1097/iae.0b013e318297f842
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Two or More Dexamethasone Intravitreal Implant Injections for Treatment of Macular Edema Related to Retinal Vein Occlusion (Shasta Study)

Abstract: Retinal vein occlusion patients treated with multiple DEX implant injections, either alone or combined with other therapies, had improved central retinal thickness and visual acuity with each subsequent injection. No new safety concerns developed with multiple implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
100
5
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 25 publications
(24 reference statements)
19
100
5
4
Order By: Relevance
“…The mean BCVA gain of +7.8 approxETDRS letters (between 1 and 2 lines in visual acuity) at 12 weeks in this study was similar to the gains in BCVA seen in previous large retrospective studies of real-world use of DEX implant in RVO [9,10]. DEX implant was effective in patients previously treated with anti-VEGF, consistent with a previous report that nine of ten patients with RVO ineffectively treated with anti-VEGF had improved BCVA and reduced CRT after DEX implant treatment [11].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The mean BCVA gain of +7.8 approxETDRS letters (between 1 and 2 lines in visual acuity) at 12 weeks in this study was similar to the gains in BCVA seen in previous large retrospective studies of real-world use of DEX implant in RVO [9,10]. DEX implant was effective in patients previously treated with anti-VEGF, consistent with a previous report that nine of ten patients with RVO ineffectively treated with anti-VEGF had improved BCVA and reduced CRT after DEX implant treatment [11].…”
Section: Discussionsupporting
confidence: 74%
“…For patients who received a second implant in this study, the mean time between the first and second implant was 155 days (approximately 5 months). This interval is consistent with the interinjection interval of 4.5 months reported in a prospective evaluation of DEX implant in patients with treatment-naïve RVO [21], and with the interinjection interval of 5.6 months reported in the SHASTA study, a large retrospective evaluation in patients with BRVO and CRVO who received at least two DEX implant injections [9]. The mean interval between DEX implant treatments was approximately 5 months (151 days) for patients in the SHASTA study who received no other treatment for RVO-associated ME during the study period [22].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Further ‘real-life' studies describing series of patients treated with Ozurdex for ME due to RVO in multicentric or single-center institutional settings have found clinically meaningful benefits and no serious adverse events [10,11,12,13,14,15,16,17,18]. However, 12-month clinical data have rarely been reported in the previous literature nor has analysis on treatment-naïve eyes with recent onset disease.…”
Section: Introductionmentioning
confidence: 91%
“…Merkoudis et al 13 found a recurrence of macular edema between months 4 and 5 after the first DEX implant in eyes treated for RVO. However, other retrospective studies found a mean reinjection interval of 4.5, 5.3, and 5.6 months after treatment with DEX implants, [14][15][16] with a probable delay between recurrence and reinjection time. However, all patients with qualitative anatomical recurrence on SD-OCT imaging had functional recurrence at 14.44 days (SD = 42.18) on average after the first signs on OCT.…”
Section: Eyementioning
confidence: 96%